Biological cycle of Lorryia formosa (Acari, Tydeidae) on rubber tree leaves: A case of thelytoky - Hernandes, F. A.; Feres, RJF; Nomura, F. (Springer, 2006)
Lorryia formosa Cooreman has been collected on many different host plants around the world. The biological cycle of this species was studied at 28 degrees C with mites collected from a rubber tree crop. The life table was constructed based on sixty individuals. The average lifetime was 37.43 +/- 20.23 (SE) days, and the r(m) was 0.08. The sex ratio was totally female biased, and unfertilized eggs developed into females. This is the first record of thelytoky in Tydeoidea proved by rearing.
Keywords: Euphorbiaceae; Hevea brasiliensis; parthenogenesis; phytophagous